Decision Support System for Eligibility of Subsidized Livable Housing Using Simple Additive Weighting Method in Pulo Village - Novia Hasdyna, Rahmat, Mardhiah, Rahmati, Asmaul Husna (LPPM-UNIKI, 2024)
Decision Support Systems (DSS) have been widely implemented in various human activities, particularly in determining eligibility for subsidized livable housing in Gampong Pulo, Samudera District, North Aceh Regency, Aceh Province, Indonesia. Currently, the evaluation process for determining eligibility for subsidized livable housing does not adhere to established criteria and relies solely on reports from the Hamlet Head and estimates, without valid supporting data. This Decision Support System is designed to facilitate decision-making in determining eligible recipients for subsidized livable housing using the Simple Additive Weighting (SAW) method. The tools employed include UML (Unified Modeling Language), with PHP (Personal Home Page) as the programming language and MySQL as the database. The results of this study demonstrate that the system simplifies the evaluation process for Gampong Pulo officials in determining eligibility for subsidized livable housing according to set criteria. This system offers several advantages over the current system, such as faster determination of aid recipients.